Measuring Work Engagement, Psychological Empowerment, and Organizational Citizenship Behavior Among Health Care Aides. (16th February 2016) - Ginsburg, Liane; Berta, Whitney; Baumbusch, Jennifer; Rohit Dass, Adrian; Laporte, Audrey; Reid, R. Colin; Squires, Janet; Taylor, Deanne
Abstract: Purpose of the Study: Health care aides (HCAs) provide most direct care in long-term care (LTC) and home and community care (HCC) settings but are understudied. We validate three key work attitude measures to better understand HCAs' work experiences: work engagement (WEng), psychological empowerment (PE), and organizational citizenship behavior (OCB-O). Design and Methods: Data were collected from 306 HCAs working in LTC and HCC, using survey items for WEng, PE, and OCB-O adapted for HCAs. Psychometric evaluation involved confirmatory factor analysis (CFA). Predictive validity (correlations with measures of job satisfaction and turnover intention) and internal consistency reliability were examined. Results: CFA supported a one-factor model of WEng, a four-factor model of PE, and a one-factor model of OCB-O. HCC workers scored higher than LTC workers on Self-determination (PE) and lower on Impact, demonstrating concurrent validity. WEng and PE correlated with worker outcomes (job satisfaction, turnover intention, and OCB-O), demonstrating predictive validity. Reliability and validity analyses indicated sound psychometric properties overall. Implications: Study results support psychometric properties of measures of WEng, PE, and OCB-O for HCAs. Knowledge of HCAs' work attitudes and behaviors can inform recruitment programs, incentive systems, and retention/training strategies for this vital group of care providers.